THE IMPLEMENTATION OF THE PROGRAM OF DRINKING WATER SUPPLY AND SANITATION-BASED SOCIETY (PAMSIMAS) IN RURAL DISTRICTS PARIAMAN KASAI RIVER SOUTH OF THE CITY PARIAMAN - PERMATA SARI, MAFALIA INTAN; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Thesiwati, SP., M.Si, Aslan Sari (Pendidikan Geografi, 2014)
AbstractsÂ This study aims to determine how the implementation of water supply and sanitation in the village community based di Desa Sungai Kasai Kecamatan Pariaman Selatan Kota Pariaman see: 1) implementation of PAMSIMAS in the village of sungai kasai, 2) the factors that affect the implementation of the program in the village of River PAMSIMAS Kasai, 3) How to realization after PAMSIMAS. Data were collected through observation, interviews, photo shoots taken in the field. Research taken using purposive sampling technique (Pointing). Test the validity of the data in triagulasi techniques that acquire data with information from several informants, at the time, place, and circumstances are different. These results indicate that: Implementation of PAMSIMAS Sungai Kasai in the Village District of Pariaman selatan is not going well is caused by several factors such as lack of water consumption as in the PAMSIMAS. Found it difficult sources of clean water and lack of community participation in the implementation of the program PAMSIMAS. Thus, to overcome these problems need the support of local governments and communities to implementation can run well.